The Role of Geoscience Education Research in the Consilience between Science of the Mind and Science of the Natural World. Issue 4 (1st November 2017) - Shipley, Thomas F.; Tikoff, Basil
ABSTRACT: This manuscript addresses the potential role of geoscience education research in understanding geoscience expert practice. We note the similarity between the perception–action framework of Ulric Neisser (Neisser, 1976) and the observation–prediction framework used by geoscience practitioners. The consilience between these two approaches is that learning takes place when links are formed between predictions and observations and that this linkage is formed through conceptual models. Use of conceptual models facilitates learning at all levels; hence, there is little difference between learning in expert practice and student learning at all levels. The field of geoscience education is uniquely poised to enhance geoscience practice through investigation of expert learning, both in traditional field research and when experts adopt new tools and techniques. The consilience of expert practice, student learning, and cognitive science outcomes provides a rich opportunity to enhance both the intellectual merit of research and the direct and indirect broader impacts.